Role of local and nonlocal interactions in folding and misfolding of globular proteins - Kumar, Adesh; Baruah, Anupaul; Biswas, Parbati (The Journal of chemical physics, 2017)
A Monte Carlo simulation based sequence design method is proposed to study the role of the local and the nonlocal interactions with varying secondary structure content in protein folding, misfolding and unfolding. A statistical potential is developed from the compilation of a data set of proteins, which accounts for the respective contribution of local and the nonlocal interactions. Sequences are designed through a combination of positive and negative design by a Monte Carlo simulation in the sequence space. The weights of the local and the nonlocal interactions are tuned appropriately to study the role of the local and the nonlocal interactions in the folding, unfolding and misfolding of the designed sequences. Results suggest that the nonlocal interactions are the primary determinant of protein folding while the local interactions may be required but not always necessary. The nonlocal interactions mainly guide the polypeptide chain to form compact structures but do not differentiate between the native-like conformations, while the local interactions stabilize the target conformation against the native-like competing conformations. The study concludes that the local interactions govern the fold-misfold transition, while the nonlocal interactions regulate the fold-unfold transition of proteins. However, for proteins with predominantly β-sheet content, the nonlocal interactions control both fold-misfold and fold-unfold transitions.